Shifts of microbial community and metabolic function during food wastes and waste activated sludge co-fermentation in semi-continuous-flow reactors: Effects of fermentation substrate and zero-valent iron. (October 2020) - Zhang, Qin; Cao, Jiashun; Wu, Yang; Zhao, Jianan; Guo, Wen; Huang, Wenxuan; Feng, Qian; Fang, Fang; Aleem, Muhammad; Luo, Jingyang
Graphical abstract: Highlights: Both FW composition and ZVI affected the VFAs production in semi-continuous reactors. The bacterial community changed little with time but varied greatly in different reactors. The metabolic functions and activities of anaerobes were linked to FW composition. The ZVI improved the metabolic activity and abundance of functional genes for VFAs. Abstract: The effects of food wastes (FW) composition and zero-valent iron (ZVI) on the volatile fatty acids (VFAs) generation, bacterial community succession and related metabolic functions during long-term FW and waste activated sludge (WAS) co-fermentation were investigated. The VFAs production in the carbohydrate-enriched reactor was approximately 3.0-folds of that in FW reactor. The ZVI contributed to the VFAs promotion by 3.6- and 6.7-folds in carbohydrate-enriched and FW reactors, respectively. Firmicutes (20.1–74.7%), Actinobacteria (0.9–26.3%), Bacteroidetes (3.4–65.7%), and Proteobacteria (9.1–28.5%) were the main bacteria in different fermentation reactors, and they were closely associated with the fermentation substrates and ZVI. Further analysis demonstrated that the key metabolic capacity (i.e. amino acid, carbohydrate and energy metabolism) and the genetic expressions of enzymes (i.e. fabA, fabZ, accA and accB) involved in VFAs generation were also related to FW composition, and were improved by the ZVI, which accounted for the significant VFAs promotion.